Standing before French Administrative Courts and Environmental protection: not specific enough for an effective access to Justice? - Chevalier, Emile (P.A. Persona e Amministrazione, 2020)
In environmental matters, under the influence of Aarhus Convention, access to court is now a core pillar for the effectiveness of environmental legislation. In the French system, the standing conditions for a claim for judicial review before the French administrative courts are usually regarded as being easily fulfilled, since the French administrative case law adopts an interest-based approach to standing. This notion is interpreted in a rather extensive manner and in such way that the requirement has been deemed as satisfied as soon as there is a link between the challenged act and the personal situation of the applicant. But, applied in environmental matters, the enforcement of those standing requirements is restrictive, since it may be rather complex to prove the existence of an individual interest to challenge an act which impacts species or biodiversity. Indeed, due to the collective dimension of environmental protection, access to judicial review for individuals might be widely impaired. Doing so, the French conception of intérêt à agir does not seem to be in compliance with high standards applicable to access to justice to review administrative action. However, despite the development of International and European standards, it is rather unlikely that the French conception may change in order to take into account the specificity of the question of access to justice in environmental matters.